2005
DOI: 10.1203/01.pdr.0000156506.03057.ad
|View full text |Cite
|
Sign up to set email alerts
|

Brain Docosahexaenoic Acid Status and Learning in Young Rats Submitted to Dietary Long-Chain Polyunsaturated Fatty Acid Deficiency and Supplementation Limited to Lactation

Abstract: N-3 fatty acid deficiency has been related to decreased docosahexaenoic acid (DHA) and increased docosapentaenoic acid (DPA) levels in brain and to learning disadvantages. The influence of n-3 deficiency and supplementation on brain fatty acids and learning were investigated in young rats. Newborn Wistar rats were assigned to three groups of cross-foster mothers. The control group (C) was nursed by mothers that received essential fatty acids during pregnancy and lactation, and the deficient group (D) was nurse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
4
29
1
Order By: Relevance
“…These results confirm other studies that have found an increased percentage of DHA in the brain following the provision of dietary supplements containing this fatty acid, and an improvement in mice's performance of the maze-learning ability test [12,13]. Garcia-Calatayud et al [14] demonstrated that young rats with a deficint supply of n-3 fatty acid limited to the lactation period presented poor memory retention in passive avoidance test directly correlated to DHA and inversely correlated to brain DPAn-6 levels. Both biochemical and functional consequences of this dietary deficiency were reversed when a supplement of DHA was administered to the deficient animals.…”
Section: Effect On Passive Avoidance Testsupporting
confidence: 90%
“…These results confirm other studies that have found an increased percentage of DHA in the brain following the provision of dietary supplements containing this fatty acid, and an improvement in mice's performance of the maze-learning ability test [12,13]. Garcia-Calatayud et al [14] demonstrated that young rats with a deficint supply of n-3 fatty acid limited to the lactation period presented poor memory retention in passive avoidance test directly correlated to DHA and inversely correlated to brain DPAn-6 levels. Both biochemical and functional consequences of this dietary deficiency were reversed when a supplement of DHA was administered to the deficient animals.…”
Section: Effect On Passive Avoidance Testsupporting
confidence: 90%
“…The passive avoidance test is a useful method to detect impairments in learning and memory and to test the capacity of memory retention in rats (Garcia-Calatayud et al 2005;Stubley-Weatherly et al 1996;Yamada et al 1983). Cognitive alterations such as deficits in learning and memory were reported following exposure to soman in animals (Buccafusco et al 1990;Choi et al 2004, Moffett et al 2011Philippens et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in Table 1, an impressive amount of evidence indicates that deficiency of n-3 PUFA, in particular DHA, during the critical developmental stages described above significantly impairs maze performance (Fedorova et al, 2009(Fedorova et al, , 2007Xiao et al, 2006;Lim et al, 2005;García-Calatayud et al, 2005;Moriguchi et al, 2000;Greiner et al, 1999), which can be restored by repletion of the n-3 PUFA in the diet at birth or weaning (García-Calatayud et al, 2005;Moriguchi and Salem, 2003) and young adult hood (Chung et al, 2008;Moriguchi and Salem, 2003). DHA cannot be replaced by its closest long-chain equivalent; n-6 PUFA docosapentaenoic acid (DPA, C22:5, n-6), as pups fed a diet rich in LA and DPA but low in DHA had impaired spatial memory performance compared to rats fed a diet rich in DHA (Lim et al, 2005).…”
Section: Moriguchi Andmentioning
confidence: 99%